Evaluating imbalances of adverse events during biosimilar development. Issue 5 (3rd July 2016) - Vana, Alicia M.; Freyman, Amy W.; Reich, Steven D.; Yin, Donghua; Li, Ruifeng; Anderson, Scott; Jacobs, Ira A.; Zacharchuk, Charles M.; Ewesuedo, Reginald
ABSTRACT: Biosimilars are designed to be highly similar to approved or licensed (reference) biologics and are evaluated based on the totality of evidence from extensive analytical, nonclinical and clinical studies. As part of the stepwise approach recommended by regulatory agencies, the first step in the clinical evaluation of biosimilarity is to conduct a pharmacokinetics similarity study in which the potential biosimilar is compared with the reference product. In the context of biosimilar development, a pharmacokinetics similarity study is not necessarily designed for a comparative assessment of safety. Development of PF-05280014, a potential biosimilar to trastuzumab, illustrates how a numerical imbalance in an adverse event in a small pharmacokinetics study can raise questions on safety that may require additional clinical trials.